PRINSIP DAN ASAS HUKUM PERKAWINAN DALAM PERATURAN PERUNDANGAN INDONESIA - Umami, Hafidhul; Nabila, Mar'atun (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2022)
Legislation in Indonesia regulates the principles and principles of marriage law. Law No. 1 of 1974 states that the purpose of marriage is to form a happy and eternal family. Marriage must also be carried out according to religious rules and be registered. The marriage law in Indonesia also adheres to the principle of monogamy, physical and psychological readiness of the bride and groom through maturity of marriage age, making divorce difficult and balancing the rights and obligations of husband and wife.